Influência da concentração polimérica em microesmulsões com álcali-surfactante-polímero (ASP) na recuperação avançada de petróleo - Alves, Helton Gomes (2021)
The Enhanced Oil Recovery (EOR) process using chemical methods, such as the Alkali, Surfactant, and Polymer (ASP) chemical systems, has been widely investigated, due to the good synergy between the three chemical agents and for presenting around 20% increase in the percentage of recovered oil in place. In this context, this paper focuses on the experimental study of microemulsified chemical systems, consisting of saponified coconut oil (surfactant), Butan-1-ol (co-surfactant), kerosene (oil phase), Na2CO3 (Alkali), water and different percentages of polymer AH 912 SH, applied as an alternative method in EOR in sandstone rock from the Botucatu sedimentary formation. Chemical systems were characterized by analysis of particle diameter, surface tension and viscosity. Rheology and adsorption tests were carried out in order to evaluate their influence on oil recovery. The flow tests in porous media were carried out in a confinement system that simulates the conditions of an oil reservoir, using sandstone rock plugs with permeability in the range of 15.70 mD to 27.66 mD and oil from the Potiguar Basin in the Ubarana area. The droplet sizes showed characteristic values of micellar aggregates, with a maximum dimension of 2.63 nm. Surface tension increased as the percentage of polymer in the systems increased. Advanced recovery tests using chemical systems showed oil displacement efficiencies with values directly proportional to the increase in viscosity of ASP chemical systems. The system with the highest percentage of polymer obtained the best percentage of oil displaced (79.12%), resulting in greater total displacement efficiency (96.07%). It was also observed that it is possible to obtain satisfactory recovery results (%OOIPt = 99,34 of and %Eda = 63,10) by injecting smaller volumes of the system, followed by brine injection. This study showed the potential of ASP microemulsion chemical systems in oil recovery.